Spirituality for the sent : casting a new vision for the missional church - Finn, Nathan A.; Whitfield, Keith S. (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2017)
"Spirituality for the Sent brings together evangelical scholars from a variety of disciplines and ecclesial traditions to address the relationship between spiritual formation and a missional vision of theology and practice. The contributors share a common vision for a missional spirituality that fosters spiritual maturity while also fueling Christian evangelism, cultural engagement, and the pursuit of justice."--Back cover.
Introduction / Nathan A. Finn, Keith S. Whitfield -- The missional church and spiritual formation / Nathan A. Finn, Keith S. Whitfield -- Spirituality, mission, and the drama of Scripture / Craig G. Bartholomew -- Missional spirituality and global Missions / Susan Booth -- Missional spirituality as congregational / Anthony L. Chute, Christopher W. Morgan -- Missional spirituality and cultural engagement / Timothy M. Sheridan, Michael W. Goheen -- Welcome to Paul's world: the contextual nature of missional spirituality / Gary Tyra -- Lament as appropriate missional spirituality / Soong-Chan Rah -- Godly love: the primary missional virtue / Diane Chandler -- Missional spirituality and worship / Gordon T. Smith -- Missional spirituality and justice / Mae Elise Cannon -- Journey in the Spirit / George R. Hunsberger.
Includes bibliographical references and indexes.
Keywords: Christian life; Spirituality -- Christianity; Missions -- Theory; Missional church movement; Mission of the church